2016
DOI: 10.1016/j.chemgeo.2016.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Celestine in a sulfidic spring barite deposit - A potential biomarker?

Abstract: We have documented the presence of celestine (SrSO4) within sediment accumulating at an artesian sulfidic spring (Zodletone Spring, Oklahoma) dominated by barite (BaSO4) precipitation associated with microbiological activity. The distribution and speciation of Sr in solid phases was determined by synchrotron-based micro-X-ray fluorescence spectroscopy and micro-X-ray diffraction, and particle morphology and texture was determined using electron microscopy. In all the natural sulphidic spring samples and lithif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Therefore, barite might have incorporated strontium in its structure. The XRD pattern of celestine is very similar to the pattern of the barite, and they can be identified together because celestine may precipitate locally within the barite crystal [44]. This presence of minor quantities of celestine within barite minerals may occur due to temperature variations during barite precipitation, which would influence the thermodynamic stability of the barite-celestine solid solution [45].…”
Section: Resultsmentioning
confidence: 83%
“…Therefore, barite might have incorporated strontium in its structure. The XRD pattern of celestine is very similar to the pattern of the barite, and they can be identified together because celestine may precipitate locally within the barite crystal [44]. This presence of minor quantities of celestine within barite minerals may occur due to temperature variations during barite precipitation, which would influence the thermodynamic stability of the barite-celestine solid solution [45].…”
Section: Resultsmentioning
confidence: 83%
“…Experimental work also demonstrated that phytoplankton may play a crucial role in bioconcentrating Ba 18 , and since sinking organic matter serves as a substrate for heterotrophic bacteria, the link between bacterial abundance and export productivity may be a key factor for Ba bioaccumulation in microenvironments in the ocean water column. Indeed, in natural environments, Ba enrichment associated with microbial biomass has been described in diverse settings, including thermal springs 15 , 16 , 20 , biofilms in the Roman Catacombs 21 , bacterial EPS at fumaroles in Solfatara Crater, Italy 22 , and in filaments of sulfide-oxidizing bacteria in marine cold seep 17 . Likewise, culture experiments demonstrated the capability of bacteria to promote barite precipitation under laboratory conditions 10 , 11 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the microbial role in precipitation of sulfates has been poorly investigated in comparison to the microbial involvement in carbonates formation, microbial barite precipitation has been described in hot springs environments, where bacteria play a role either in oxidizing sulfur compounds to generate sulfate or in accumulating Ba in microbial mats 15 , 16 . In marine environments, bacterial involvement in barite formation has recently been reported for a cold seep where barite precipitated on filaments of sulfide-oxidizing bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the geochemical importance of marine (Ba x , Sr 1−x )SO 4 formation, two paradoxes still exist. First, the global oceans are undersaturated with respect to barite, while barite is extensively present in seawater column and marine sediments (5,7,8). Second, Sr-rich marine barite (>50 mol% strontium) formation (7,9) is not thermodynamically favorable (7,10), as the solubility of SrSO 4 (K sp,SrSO4 = 10 −6.63 ) is three orders of magnitude higher than BaSO 4 (K sp,BaSO4 = 10 −9.98 ) (3,10).…”
mentioning
confidence: 99%